An Innovative, Cross-Disciplinary Approach to Promoting Child Health: The Reggio Emilia Approach and the Ecological Approach to Family Style Dining Program. Issue 1 (2nd January 2019) - Dev, Dipti A.; Burton, Anna; McBride, Brent A.; Edwards, Carolyn Pope; Garcia, Aileen S.
Abstract : The Reggio Emilia approach is an international example of high-quality early care and education programs and this article offers innovative, practical strategies in which Reggio Emilia-inspired educators can link this approach while implementing the research-based EAT Family Style Dining program to foster a positive mealtime environment and promote better health for children.